Wireless Passive High-Temperature Sensor Readout System for Rotational-Speed Measurement. (2nd November 2021) - Hong, Yingping; Jia, Pengyu; Guan, Xihao; Xiong, Jijun; Liu, Wenyi; Zhang, Huixin; Li, Chen
Abstract : Rotational-speed measurement in harsh environments is an important topic. However, the high rotation results in rapid frequency variations in the signals of a sensor and changes in physical properties under extreme thermal circumstances cause significant difficulties in reading signals. To address this problem, we adopt wireless passive measurement methods to design a special characteristic signal circuit module that achieves precise measurement of rotational speed at high temperatures. The sensor and the readout system include a variable frequency source, a readout antenna, and a radio frequency demodulation circuit. Herein, a demodulation detector of the signal conversion circuit is designed and used in the envelope detection module of the single sideband demodulation method. In addition, a conversion circuit test platform for high-temperature environment sensor signal is developed. From the testing, the output signal demodulation of the sensor was observed under a maximum temperature of 700°C with error less than 0.12%. The new sensor and measurement method do not require physical leads and achieve wireless noncontact accurate measurement of rotational speed at high temperature.